2008
DOI: 10.1016/j.carbon.2008.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Positional control of catalyst nanoparticles for the synthesis of high density carbon nanofiber arrays

Abstract: Precise arrangement of nanoscale elements within larger systems, is essential to controlling higher order functionality and tailoring nanophase material properties. Here, we present findings on growth conditions for vertically aligned carbon nanofibers that enable synthesis of high density arrays and individual rows of nanofibers, which could be used to form barriers for restricting molecular transport, that have regular spacings and few defects. Growth through plasma-enhanced chemical vapor deposition was ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Such membranes have been made using self-assembled nanowires, 4 colloidal selfassemblies, 5 amorphous silicon (a-Si) to porous nanocrystalline silicon (pnc_Si) crystallization, 6 and vertically aligned carbon nanofibers. [7][8][9][10][11] These membranes still rely on restricting transport with implementation of tortuous paths that molecules must take to pass through the membrane. The distribution of effective pore size depends on the thickness of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Such membranes have been made using self-assembled nanowires, 4 colloidal selfassemblies, 5 amorphous silicon (a-Si) to porous nanocrystalline silicon (pnc_Si) crystallization, 6 and vertically aligned carbon nanofibers. [7][8][9][10][11] These membranes still rely on restricting transport with implementation of tortuous paths that molecules must take to pass through the membrane. The distribution of effective pore size depends on the thickness of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 demonstrates that vessels are defect free and have a functional pore size, and size distribution between 100nm and 350nm. In previous work we examined the use of patterned carbon nanofiber membranes for similar separations, but found that defect density resulting from the nanofiber growth resulted in “leaky” membrane structures 25, 26 . In addition to being free of defects, the deterministic nature of the structures used here help make modeling and simulation of these systems more tractable.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work we examined the use of patterned carbon nanofiber membranes for similar separations, but found that defect density resulting from the nanofiber growth resulted in ''leaky'' membrane structures. 25,26 In addition to being free of defects, the deterministic nature of the structures used here helps to make modeling and simulation of these systems more tractable. This basic demonstration helps illustrate the potential utility in using the reaction vessels to exclude molecules or functionalized particles based on size.…”
Section: Functional Demonstration Of Size Exclusion and Molecular Con...mentioning
confidence: 99%
“…Dispersions of nanoparticles are becoming a ubiquitous element of everyday life, and are the subject of intensive scientific investigation. Applications have been developed spanning the breadth of: pharmaceuticals such as cancer treatment 1 and drug delivery systems 2 ; antibacterial and anti-fouling coating materials 3 ; improved cosmetics formulations 3 ; stronger construction materials 4 ; and numerous other technologies 5 10 , representing a huge expenditure of human resources and effort. Furthermore, nanoparticles of scientific interest are not uniquely synthetic.…”
Section: Introductionmentioning
confidence: 99%